2017
DOI: 10.1016/j.pt.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA Replication in Trypanosomatids: There Are No Easy Methods for Solving Difficult Problems

Abstract: In trypanosomatids, etiological agents of devastating diseases, replication is robust and finely controlled to maintain genome stability and function in stressful environments. However, these parasites encode several replication protein components and complexes that show potentially variant composition compared with model eukaryotes. This review focuses on the advances made in recent years regarding the differences and peculiarities of the replication machinery in trypanosomatids, including how such divergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 96 publications
(168 reference statements)
1
33
0
Order By: Relevance
“…In addition, while SNS-seq has been performed in asynchronous cells, MFA-seq has been used with enriched populations for specific cell cycle populations. Nonetheless, it remains unclear if and how the considerably variant predictions of DNA replication activity by these different methodologies can fit together (discussed at length in recent reviews) (72,74,81). Having said this, it is very possible that the description of subtelomeric DNA replication provides at least a partial explanation for single DNA molecules, visualised by DNA combing, that display two regions of DNA synthesis (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while SNS-seq has been performed in asynchronous cells, MFA-seq has been used with enriched populations for specific cell cycle populations. Nonetheless, it remains unclear if and how the considerably variant predictions of DNA replication activity by these different methodologies can fit together (discussed at length in recent reviews) (72,74,81). Having said this, it is very possible that the description of subtelomeric DNA replication provides at least a partial explanation for single DNA molecules, visualised by DNA combing, that display two regions of DNA synthesis (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…TRYPANOSOMATIDS are unicellular eukaryotic parasites considered to be evolutionarily successful, not only for their ability to infect numerous types of organisms but also because they diverged early in the evolutionary scale, approximately 200-500 million years ago (El-Sayed et al 2005;Flegontov et al 2013;da Silva et al 2017;Simpson et al 2004). These organisms are represented by the agent of African sleeping sickness, Trypanosoma brucei, several species of Leishmania spp., which cause distinct types of leishmaniasis, and the etiological agent of Chagas disease, Trypanosoma cruzi.…”
mentioning
confidence: 99%
“…However, none of these studies indicated that replication-transcription conflicts contributed to the firing of origins, which, in model eukaryotes, is an apparently wellregulated event (6). Based on this, we have proposed that DNA damage is generated after replication and transcription find each other in conflicting directions, which signals to initiate the phosphorylation of a nearby histone H2A, either by ATR or ATM kinases (14,34,78). Moreover, the hybrid R-loop structure is likely formed and maintained in the collision region.…”
Section: Discussionmentioning
confidence: 99%
“…However, the same study identified many more ORC binding sites than activated origins (16), which can be easily explained by the fact that MFA-seq (genome-wide analysis) is a technique that provides a result based on population analysis. Thus, the set of activated origins that matches with ORC binding sites can be classified as constitutive, and the remaining ORC binding sites are probably potential sites for the firing of non-constitutive origins (flexible or dormant) (6,14).…”
Section: Edu Allows a More Accurate Estimation Of S Phase Duration Inmentioning
confidence: 99%
See 1 more Smart Citation